Normative data for lower limb peak mechanical power in children aged 7 to 11 years old - Nicholas Owen (Journal of Comorbidity, 2015)
Aim: There are currently about 45 published instruments for the assessment of motor development in children. However, all of the tests lack robust evidence of reliability and validity. A high levels of lower limb peak muscular power (Pmp) is widely considered a key determinant of athletic performance; conversely it is reasonable to assume that poor physical performance, characterised by poor coordination, would be associated with low levels of Pmp. However there are currently limited valid data on normative values of Pmp in children. The aim of this study was to report valid normative data for Pmp in children.Method: Children 7 to 11 years old (n= 791, age 9.26 ± 1.20 decimal years, stature = 1.338 ± 0.094 m, body mass = 34.7 ± 9.7 kg) of mixed gender were randomly selected from schools in South Wales. Each child performed one countermovement jump (CMJ) off a force platform with their hand held on their hips to isolate the lower limbs. The ground reaction force was recorded and the momentum impulse principle was used to derive a criterion measure of lower limb peak instantaneous power (Pp).3 A pilot study had shown good reliability for Pp in children in this age range (ICC > 0.92). Participants were grouped in school years (Y) and comparisons were made between genders and year groups for Pp.Results: There was no significant difference in Pp between genders for year group (p = 0.05). Combined gender groups for each school year produced Pp that were normally distributed and had the following values (mean Pp, standard deviation), Y3 = 905 ± 191 W, Y4 = 1047 ± 233 W, Y5 = 1230 ± 258 W, Y6 = 1367 ± 326 W. A significant difference in Pp was found between successive mixed gender year groups (p= 0.01). Y3 (n= 190) to Y4 (n = 182), t = 6.01, p < 0.001, Y4 to Y5 (n = 215), t = 7.67, p < 0.001, Y5 to Y6 (n = 204), t = 3.94, p < 0.001.Discussion: This study indicates that Pp produced in a single-trial CMJ has the potential to provide information on the coordination of children aged 7 – 11 years, with a high level of discrimination. For example, in Y3 (aged 7-8 years) there is a 12% increase in Pp between the 5th and 10th percentile. Pp as measured in a CMJ has the potential to augment tests like Movement Assessment Battery for Children-2. However more study is needed regarding the potential benefits of allometric scaling of Pp and further splitting school year groups into 3 month groups and comparison with other tests of physical ability.